2012
DOI: 10.1371/journal.pone.0030063
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Dystrophic Skeletal Muscle by PGC-1α Involves a Fast to Slow Fiber Type Shift in the mdx Mouse

Abstract: Increased utrophin expression is known to reduce pathology in dystrophin-deficient skeletal muscles. Transgenic over-expression of PGC-1α has been shown to increase levels of utrophin mRNA and improve the histology of mdx muscles. Other reports have shown that PGC-1α signaling can lead to increased oxidative capacity and a fast to slow fiber type shift. Given that it has been shown that slow fibers produce and maintain more utrophin than fast skeletal muscle fibers, we hypothesized that over-expression of PGC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
203
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(229 citation statements)
references
References 64 publications
18
203
2
Order By: Relevance
“…Interestingly, as this article was in preparation, it was shown that chronic RSV administration also tended to increase utrophin A protein content in dystrophic skeletal muscle (56). Around the same time, others found that while RSV treatment induced utrophin A mRNA expression, the drug had no effect on utrophin A protein levels (19,20).…”
Section: MDXmentioning
confidence: 82%
See 3 more Smart Citations
“…Interestingly, as this article was in preparation, it was shown that chronic RSV administration also tended to increase utrophin A protein content in dystrophic skeletal muscle (56). Around the same time, others found that while RSV treatment induced utrophin A mRNA expression, the drug had no effect on utrophin A protein levels (19,20).…”
Section: MDXmentioning
confidence: 82%
“…In a preclinical model of DMD, treatment of mdx mice with RSV evokes beneficial adaptations in skeletal muscle (19,20,29,56). However, data on whether RSV induces skeletal muscle remodeling in mdx animals toward slower, more oxidative characteristics are clearly lacking and remain fragmentary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Force generation at 90 and 100 Hz did not differ in any muscle studied, and the force was normalized to the isometric tetanus at 100 Hz to generate force-frequency curves. Second, soleus muscles were subjected to a fatigue test, as previously described (34). Briefly, muscles were stimulated once per second for 10 min (200-s pulse, 100 Hz, 330-ms duration) to determine resistance to fatigue.…”
Section: Methodsmentioning
confidence: 99%